The Effect of Service Quality and Promotion on Customer Satisfaction at Perumda BPR Bank Daerah Lamongan - Ainur Rofiqoh; Abid Muhtarom; Mohammad Yaskun (Sean Institute, 2025)
This study aims to find out 1) The effect of service quality on customer satisfaction, 2) The effect of promotion on customer satisfaction at Perumda BPR Bank Daerah Lamongan. The population in the study is customers who save at Perumda BPR Bank Daerah Lamongan. Meanwhile, the sample used was 78 respondents with a sampling technique using purposive sampling. From the results of the t-test, the service quality variable was obtained tcal (12.010) > ttable (1.99167), the promotion variable was obtained tcount (2.001) > ttable (1.99167). The results of the Fcal test (215,367) > Ftabel (2.73). From the multiple linear test Y = it can be seen that the most dominant value is the quality of service of 0.118. From the results of the above research, it can be concluded0,001+0,118X^1+0,103X^2+e, that the variables of Service Quality, Promotion partially have a positive and significant effect on Customer Satisfaction at Perumda BPR Bank Daerah Lamongan. Ftest test shows that Service Quality, Promotion simultaneously have a significant effect on Customer Satisfaction at Perumda BPR Bank Daerah Lamongan. And the most dominant variable of service quality is the Lamongan Regional Bank.